ANALISIS TIMBANGAN PADA HOTPLATE MANGNETIC STIRRER BERBASIS ARDUINO UNO - Abdillah, Khairil; Supandi; Naibaho, Hengky Herdiansyah (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2022)
Hotplate magnetic stirrer is a tool used to homogenize and heat a solution, this tool is used in microbiology, chemistry and pharmaceutical laboratories to homogenize and heat a solution. The main component of the hotplate magnetic stirrer is the stepper motor which functions to rotate the sample and heat it using a heater at a predetermined speed and time. The hotplate magnetic stirrer that the author made uses an Arduino uno At mega 328p microcontroller, a motor driver, a 20x4 LCD, a buzzer and a keypad. the motor driver is used to adjust the motor speed according to the user's wishes, the LCD functions to display the motor speed and timer, the buzzer will sound when the magnetic stirrer hotplate is turned on and when the keypad is pressed, the loadcall functions as a sensor used to detect the pressure that is placed on the plate , the HX711 module functions to convert measured changes in resistance changes and convert them into voltage quantities through existing circuits, keypads as speed and timer inputs. When the speed has been reached, the motor driver will work to control the motor to keep it according to the desired speed.